Analysing funding costs advantages using European primary market bond yield spreads - Peter Bednarek; Christoph Roling (Deutsche Bundesbank, 2021)
This analysis studies the evolution of funding costs of banks from 28 European countries (EU28) in the primary bond market before and after the great financial crisis of 2007-2009 and the European sovereign debt crisis of 2011-2012. Based on the Centralised Securities Data Base (CSDB) our main findings can be summarized as follows. The funding costs for systemically important banks (SIBs) and non-SIBs displays similar dynamics during the sample period from 2000 to 2019. For both of these two groups, funding costs were comparatively low between 2003 and 2006, albeit higher for SIBs than for non-SIBs, increased significantly between 2007 and 2011, and then gradually decreased after 2011, even tough to a higher level than before the crisis. The increase in funding costs during the crisis was larger for the SIBs than for the non-SIBs, while after the crisis, these dynamics have reversed: funding costs have decreased more quickly for SIBs than for non-SIBs.
Keywords: G01; G12; G21; G28; L51; 330; too-big-to-fail; funding costs (advantages); primary market bond market (yield spreads); (global) systemically important banks; great financial crisis; European sovereign debt crisis; Bank Recovery and Resolution Directive